Emerging Market Entry: The Case of the Low-Cost Airlines in Ukraine and other CIS Countries - Krasnova, Olena (2008)
In the last two decades a new form of air transport has emerged and quickly proliferated in Europe - Low Cost Carriers (LCC). Major players in this new sector such as RyanAir and Easy Jet have grown from marginal charter-like air transport providers into larges European carriers with passenger volumes approaching 50 million travelers per year. The business model utilized was not new, being copied from a highly successful US carrier SouthWest. The main idea is to offer a "no frills" service at a cost of about 50% of what traditional air carriers would offer on a similar route. This results in significant increases in passenger volumes, attracting travelers who were earlier unable to afford air transport. High passenger volumes imply significant cash flows, which, as practice shows, results in profits often larger than those of traditional carriers with their high operating costs.